2014
DOI: 10.1093/jxb/eru251
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+-induced changes at the root level account for the increased tolerance of acclimated tobacco plants

Abstract: SummaryExposing plants to non-toxic metal concentrations elicits specific detoxification mechanisms in tobacco roots that improve root membrane functionality and leaf stomatal regulation with toxic zinc in the growing medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 50 publications
2
19
0
4
Order By: Relevance
“…S2b), these results support the view that photosynthesis was initially limited by CO 2 diffusion as a consequence of low leaf stomatal conductance ( Medrano et al, 2002). This result is in accordance with the increasing evidence suggesting that exposure to toxic metal concentrations initially affects plant water relations (Barcelo and Poschenrieder, 1990;Sagardoy et al, 2010;Bazihizina et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…S2b), these results support the view that photosynthesis was initially limited by CO 2 diffusion as a consequence of low leaf stomatal conductance ( Medrano et al, 2002). This result is in accordance with the increasing evidence suggesting that exposure to toxic metal concentrations initially affects plant water relations (Barcelo and Poschenrieder, 1990;Sagardoy et al, 2010;Bazihizina et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…It has been found that the leaf area decreased in P. vulgaris exposed to Cd (Barcel贸 et al 1986a(Barcel贸 et al , 1988, C. sativus treated with Cu (Vinit-Dunand et al 2002) and Nicotiana tabacum subjected to an excess of Zn (Bazihizina et al 2014). In P. Fig.…”
Section: Effects Of Heavy Metals On Transpiratory Water Lossmentioning
confidence: 98%
“…If soils are high in soluble salts (including heavy metal salts), the osmotic potential in the soil solution might be lower than the potential of the cell sap in root. Under these circumstances, the soil solution would severely restrict the rate of water uptake by plants Barcel贸 et al (1986a) Leaf Phaseolus vulgaris Becerril et al (1989) Leaf Medicago sativa Becerril et al (1989) Leaf Triforium pratense Poschenrieder et al (1989) Leaf Helianthus annuus Kastori et al (1992) Root, shoot Oryza sativa Moya et al (1993) Shoot Lactuca sativa Costa and Morel (1994) Shoot Lupinus albus Costa and Morel (1994) Shoot Pisum sativum Hern谩ndez et al (1997) Leaf Silene vulgaris Schat et al (1997) Leaf Hordeum vulgare Vassilev et al (1997Vassilev et al ( , 1998 Kholodova et al (2005Kholodova et al ( , 2011 Root Nicotiana tabacum Bazihizina et al (2014) Root, shoot Beta vulgaris Sagardoy et al (2010) Mesembr. cryst.…”
Section: Effects Of Heavy Metals On Water Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…A. halleri plants grown hydroponically accumulate metal ions in the cell wall of the rhizodermis mainly as Zn/Cd phosphate precipitates [95]. Excessive concentrations of metals have negative and even toxic effects on the plasma membrane of root cells, expressed as disturbed membrane functionality, which causes changes in membrane potential (E M ) and increased plant water loss [96,97]. The effects of divalent metal cations such as Cd 2+ and Zn 2+ on E M differ mainly according to the available heavy metal concentration, to its affinity status and mode of action [97,98].…”
Section: Mechanisms Involved In Zn Tolerance and Hyperaccumulationmentioning
confidence: 99%